The Timing of Electoral Funding on Women´s Campaigns - Scheidweiler, Gerson (2022)
This article investigates the influence of electoral financing quotas in Brazil on women’s access to resources to execute campaign strategies. Academic literature indicates the importance of money as one of the main factors that aides in the success of a candidacy. Historically, money has been less accessible in women’s campaigns. Thus, for this research, a quantitative analysis was carried out in the database of the Superior Electoral Court of Brazil to verify when the allocation of funds were destined to the men versus the women who ran for the Chamber of Deputies in the 2014 and 2018 elections. The results indicate that the financial resources passed on by political parties are made available to women later in a campaign than to men. The later timingaround financial allocation hinders women's ability to plan and execute their electoral campaigns.